Post a New Question

Math

posted by on .

(2x+1)(x-5)-(4x+2)(3x+7)+(1+2x)

  • Math - ,

    = 2x^2 - 10x + x - 5 -(12x^2 + 28x + 6x + 14) + 1+2x
    = -10x^2 - 41x -18

  • Math - ,

    Is that factorization?

  • Math - ,

    no, what I did is called expanding.

    (x+1)(x-2) = x^2 - x - 2 ------> expanding (take brackets away)
    x^2 - x - 2 = (x+1)(x-2) ------> factoring (put brackets in)

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question